Canned pork adobo rice - Florcruz, Maria Katrina Manahan; Azanza, Ma. Patricia V. (2001., 2001)
The study aimed to establish a thermal process for canned pork adobo rice. Phase I of the study dealt with the formulation used for the pork adobo rice meal was developed by selecting the most acceptable pork adobo formulation from recipes of private individuals and subsequently modifying the selected pork adobo formulation based on panelists comments. The pork adobo formulation developed in this part of the study included meat cuts in 1 cm3 dimensions that were moderately dark brown in color and had strong dstinct adobo flavor. Phase I also established a 30:70 pork adobo to rice ratio for the pork adobo rice meal using IR42 cultivar as the basal rice. The thermal process for canned pork adobo rice was established in Phase II. The pre-canning steps for the basal rice were washing, hydration, pre- gelatinization and addition of an emulsion-surfactant mixture. Water acidified with acetic acid solution (pH= 4.2±0.1) was used as the soaking, pre-gelatinization and suspending medium for the basal rice. The pork adobo formulation developed in Phase I of the study was also modified in Phase II in order for the pork adobo to be more suitable as a topping for the basal rice. The further modified pork adobo formulation was cooked until dry and had meat cuts in 〖30cm〗^3 dimensions. The calculated thermal process determined using Ball's mathematical method was 45.87 min at (115.6°C). The basal rice of the canned pork adobo rice was still judged as excessively cohesive and disintegrated while he pork adobo topping had a light brown color with predominant vinegar, garlic and peppercorn aroma. The effects of using less amounts of water for the pre-canning steps of the basal rice and the use of lean meat in the pork adobo topping were recommended for further studies
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Canned pork